The Analysis of Barriers to the Use of Physics Practicum Applications - Ramayani, Novi; Amalia, Lia (International Journal of Education and Teaching Zone, 2022)
This research aims to analyze the conflicts or obstacles faced by students and physics teachers in carrying out physics practicum activities at SMP Negeri 5 Jambi City. This Research Means Narrative Research Using Mix Method. The sample in this study was 35 students and two subject physics teachers. Data Collection Using Angel Teachers and Students About Physics Practicum Applications And Interview Guide Sheets To Teachers. This study uses narrative statistical analysis techniques for quantitative data and uses the example of Miles and Huberman for qualitative data. The research results based on the questionnaire of students and teachers showed that the implementation and assessment of the physics practicum and student motivation were in a suitable category, while the teacher's motivation was in a bad category. Then from what will happen in the interview, problems are obtained in the implementation of the physics practicum, namely the laboratory room, which is still used as a shared room, not enough time to carry out the practicum, the lack of teacher motivation, and the number of practicum senses that are less evenly distributed.